Type 1 diabetes impairs the activity of rat testicular somatic and germ cells through NRF2/NLRP3 pathway-mediated oxidative stress - Venditti, Massimo; Romano, Maria Zelinda; Boccella, Serena; Haddadi, Asma; Biasi, Alessandra; Maione, Sabatino; Minucci, Sergio (Frontiers in Endocrinology, 2024)
Background: It is well known that metabolic disorders, including type 1 diabetes (T1D), are often associated with reduced male fertility, mainly increasing oxidative stress and impairing hypothalamuspituitary-testis (HPT) axis, with consequently altered spermatogenesis and reduced sperm parameters. Herein, using a rat model of T1D obtained by treatment with streptozotocin (STZ), we analyzed several parameters of testicular activity. Methods: Ten adult male Wistar rats were divided into two groups of five: control and T1D, obtained with a single intraperitoneal injection of streptozotocin. After three months, rats were anesthetized, and sacrificed; one testis was stored at -80° C for biochemical analysis, and the other was fixed for histological and immunofluorescence analysis. Results: Data confirmed that T1D induced oxidative stress and, consequently alterations in both testicular somatic and germ cells. This aspect was highlighted by enhanced apoptosis, altered steroidogenesis and Leydig cell maturity, and impaired spermatogenesis. In addition, the blood-testis barrier integrity was compromised, as showed by the reduced levels of structural proteins (N-Cadherin, ZO-1, occludin, connexin 43, and VANGL2) and the phosphorylation status of regulative kinases (Src and FAK). Mechanistically, the dysregulation of the SIRT1/NRF2/MAPKs signaling pathways was proved, particularly, the reduced nuclear translocation of NRF2, affecting its ability to induce the transcription of genes encoding for antioxidant enzymes. Finally, the stimulation of testicular inflammation and pyroptosis was also confirmed, as highlighted by increased levels of some markers, such as NF-κB and NLRP3.The combined data allowed us to confirm that T1D has detrimental effects on rat testicular activity. Moreover, a better comprehension of the molecular mechanisms underlying the association between metabolic disorders and male fertility could help to identify novel targets to prevent and treat fertility disorders related to T1D.